Pendampingan Membuat Media Pembelajaran Visual dengan Canva Pada Raudhatul Athfal Al Muttaqin - Sri Hadianti; Nissa Almira Mayangky; Ridan Nurfalah; Nita Merlina (SWAGATI : Journal of Community Service, 2025)
This community service activity aims to enhance the skills of teachers at Raudhatul Athfal (RA) Al Muttaqin in creating engaging and interactive visual learning materials using the Canva application. These skills are considered crucial to supporting a more creative and effective learning process, particularly for young children who tend to learn through visual media. The method used in this activity is a workshop that includes an introduction to the Canva application, hands-on practice in creating various learning materials such as educational posters and infographics, as well as evaluation and mentoring sessions. The outcomes of this activity are expected to improve the creativity of the teachers at RA Al Muttaqin, increase the appeal of teaching materials, and provide a more enjoyable learning experience for children. Thus, this activity is anticipated to make a positive contribution to the quality of education at RA Al Muttaqin and serve as a foundation for sustainable collaboration between Universitas Nusa Mandiri and educational institutions in the Bekasi area.